Till Debt Do Us Part: Strategic Divorces and a Test of Moral Hazard - Yeorim Kim; Mauro Mastrogiacomo; Stefan Hochguertel; Hans Bloemen (Institute of Labor Economics (IZA), 2022)
We test whether households that face prospective home equity losses during a house price downturn use divorce to shed debt. We study the Dutch context, where qualifying homeowners can buy into a mortgage guarantee scheme that insures the lender against borrower default and transfers the risk to the public. Divorce is one of the major events that obliges the guarantor to repay outstanding residual debt after (foreclosure) sale. We argue in this paper that divorce is endogenous to holding underwater mortgages, and hence constitutes a choice that can be used for strategic use of the insurance. Using administrative data, we find a significant, 44% increase in the probability to divorce for households with an underwater mortgage. This effect is causal to being insured. The identification relies on a regression discontinuity design, that exploits the fact that the insurance is only available for properties with values below a legislated qualification threshold. The house price crisis (2008-2013) provides an unexpected shock to house values, leaving about 40% of owners with an underwater mortgage. Their home equity averages to about exteuro-50.000. Couples with similar characteristics just above the qualification threshold experienced significantly less often a divorce than couples just below the threshold. We interpret this behavioral response as moral hazard, also because the induced divorcees reunite at a higher rate than other divorcees.
Keywords: D10; G21; G52; J12; 330; moral hazard; mortgage insurance; divorce